Diverse tritepenoids from the fruits of Walsura robusta and their reversal of multidrug resistance phenotype in human breast cancer cells. (April 2017) - Zhang, Yao; An, Fa-Liang; Huang, Shan-Shan; Yang, Lei; Gu, Yu-Cheng; Luo, Jun; Kong, Ling-Yi
Abstract: Four 18 (13 → 14)- abeo limonoids, five cedrelone limonoids, and five walsurin limonoids were isolated from the fruits of Walsura robusta together with 21 known compounds. Their structures were determined by extensive studies of their one- and two-dimensional NMR spectra and mass spectroscopy results. Among all the isolated compounds, the absolute configurations of 11-oxo-dihydrocedrelone, walsuronoid B, dysoxylumosin G, and walsunoid H were confirmed by single crystal X-ray diffraction. Selected compounds were evaluated for their reversal of multidrug resistance (MDR) phenotype in human breast cancer cells in vitro . Walsurin A showed significant effect in sensitization of these resistant cancer cells at non-toxic concentration to doxorubicin with the modulation factor of 62.76. Graphical abstract: The phytochemical investigation of Walsura robusta extract yield 35 triterpenoids. Walsurin A showed a significant effect in sensitization of the multidrug resistance phenotype in human breast cancer cells in vitro . Highlights: 35 triterpenoids were isolated from the fruits of Walsura robusta. The structures of the 14 compounds were established by spectroscopic analyses, and by X-ray crystallography for 4 of the 35 compounds. Selected compounds were evaluated for their reversal of multidrug resistance phenotype in human breast cancer cells in vitro .